A circle of life: platelet and megakaryocyte cytoskeleton dynamics in health and disease - Haonan Liu; Julie P. I. Welburn (Open Biology, 2024)
Platelets are blood cells derived from megakaryocytes that play a central role in regulating haemostasis and vascular integrity. The microtubule cytoskeleton of megakaryocytes undergoes a critical dynamic reorganization during cycles of endomitosis and platelet biogenesis. Quiescent platelets have a discoid shape maintained by a marginal band composed of microtubule bundles, which undergoes remarkable remodelling during platelet activation, driving shape change and platelet function. Disrupting or enhancing this process can cause platelet dysfunction such as bleeding disorders or thrombosis. However, little is known about the molecular mechanisms underlying the reorganization of the cytoskeleton in the platelet lineage. Recent studies indicate that the emergence of a unique platelet tubulin code and specific pathogenic tubulin mutations cause platelet defects and bleeding disorders. Frequently, these mutations exhibit dominant negative effects, offering valuable insights into both platelet disease mechanisms and the functioning of tubulins. This review will highlight our current understanding of the role of the microtubule cytoskeleton in the life and death of platelets, along with its relevance to platelet disorders.